APPLICATION OF MAJR AGGREGATE MEASURE IN THE GOVERNANCE QUALITY TESTING IN THE EU-28 - Miłaszewicz, Danuta; Nermend, Kesra (Metody Ilościowe w Badaniach Ekonomicznych, 2014)
The type of governance applied in an economy as well as its quali_x0002_ty determines the quality of life. Decisions that result in the improved gover_x0002_nance quality should be preceded by operationalisation of this category and by the related research. The purpose of this article is to present the concepts of governance and good governance as well as to propose the application of an aggregate measure of the governance quality constructed on the basis of the World Bank indices in the time cross-sectional analysis of 28 EU member states over the period of 2002-2012.